MULTI-SCALE OROGRAPHIC FORCING OF THE ATMOSPHERE LEADING TO AN EROSION EVENT - Ólafsson, Haraldur; Háskóli Íslands (University of Iceland), Veðurstofa Íslands (Icelandic Meteorological Office) and Reiknistofa í veðurfræði (Institute for Meteorological Research); haraldur@vedur.is (Croatian meteorological society; info@meteohmd.hr, 2005)
Abstract: A satellite image of blowing dust is compared to a simulation of winds during a major erosion event in Iceland. There is large spatial variability in the wind speed and this variability is attributed to the topography. The atmosphere responds particularly stongly to the mountains because of a low-level inversion which is a result of synoptic-scale descent from the Greenland ice cap. The simulation is a part of the new MM5-based forecast system in Iceland (HRAS) and comparison with the patterns revealed by the dust image indicates that all main features of the flow are correcty reproduced by the forecast system. This case study indicates that local enhancment of the wind may be important for erosion.